Kelas Laktasi Sebagai Media Pendidikan Gizi Ibu Menyusui - Ibnu Zaki; Widya Ayu Kurnia Putri (Universitas Jenderal Soedirman, 2021)
The problem of under-five malnutrition is a challenge in improving public health. For infants, growth and development is influenced by the amount of nutrients consumed. Most of these nutritional needs can be met with adequate breastfeeding. Consumption of breast milk, apart from being the main source of energy, also fulfills the needs of protein, vitamins and minerals. Knowledge related to nutrition and breastfeeding is low which is the cause of the practice of exclusive breastfeeding is still low. Nutrition education is an effort to increase the knowledge of the target audience. Nutrition education in lactation classes is an alternative solution to solving the problem of low knowledge of pregnant women. This activity aims to increase knowledge related to breastfeeding through lactation classes so that the target audience is able to carry out good practices and is motivated to provide exclusive breastfeeding. The method used was nutrition education through lectures and discussions with the help of leaflets and flipcharts. The results of the activity evaluation showed that there was an increase in the average knowledge score from 12.07±1.25 to 14.40±0.52 (P < 0.05). Nutrition education in lactation classes increases knowledge of pregnant women.Keywords: Exclusive Breastfeeding, Nutrition Education, Malnutrition, Pregnant Women, Lactation Class